MODELING THE Fe K LINE PROFILES IN TYPE I ACTIVE GALACTIC NUCLEI WITH A COMPTON-THICK DISK WIND - Tatum, M; Turner, T; Sim, SA; Miller, L; Reeves, J; Patrick, A; Long, K (Institute of Physics Publishing, 2012)
We have modeled a small sample of Seyfert galaxies that were previously identified as having simple X-ray spectra with little intrinsic absorption. The sources in this sample all contain moderately broad components of FeK-shell emission and are ideal candidates for testing the applicability of a Compton-thick accretion disk wind model to active galactic nucleus (AGN) emission components. Viewing angles through the wind allow the observer to see the absorption signature of the gas, whereas face-on viewing angles allow the observer to see the scattered light from the wind. We find that the FeK emission line profiles are well described with a model of a Compton-thick accretion disk wind of solar abundances, arising tens to hundreds of gravitational radii from the central black hole. Further, the fits require a neutral component of FeKα emission that is too narrow to arise from the inner part of the wind, and likely comes from a more distant reprocessing region. Our study demonstrates that a Compton-thick wind can have a profound effect on the observed X-ray spectrum of an AGN, even when the system is not viewed through the flow. © 2012. The American Astronomical Society. All rights reserved..